Gambaran Pengetahuan Tentang Kebutuhan Nutrisi Pada Masa Nifas Di Puskesmas Tanete Kabupaten Bulukumba - Haerani Haerani; Sumarni Sumarni; Indra Inranda Reski; Fitri fitri (Journal Of Midwifery And Nursing Studies, 2021)
Increasing the importance of nutrition the department of health has a program related to health for mothers and children by increasing nutrition for postpartum mothers related to nutritional needs during the puerperium. However, there is one factor that can be a problem and can hamper the process of maternal nutritional needs, namely the mother only takes care of the child with the mother paying more attention to the nutrition of the child consumes. The purpose of this study is to find out the description of postpartum mothers' knowledge about the nutritional needs of the puerperium at a good, sufficient, and less level. This type of research is a descriptive research method, namely research conducted with the main objective to make a picture or description of the situation objectively. The location of this research was at Tanete Health Center in May-July 2019. The population in this study was all postpartum mothers with a sample of 40 people with a total sampling technique. The variable in this study was the mother's knowledge of nutrition needs. The results showed that of the 40 respondentsnthere were 2 respondents (5%), had a good level of knowledge, 22 respondents (55%) had enough knowledge, and 16 respondents (40%) had a sufficient level of knowledge due to the majority of respondents working as houswives who only take care of her husband and child.